The effectiveness of e-learning as a component of higher education (on the basis of quantitative meta-analysis) - Mirontsov, Igor V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The comparison between the effectiveness of online-learning and traditional education was discussed. Using the technique of quantitative meta-analysis on the basis of experimental data it was shown that e-learning can be an effective and independent component of higher education. The thesis of the need to start an expert discussion on the prospects for the introduction of online forms of education for the «massive online course» format (MOCC) in higher educational institutions of Belarus is separately discussed.
Keywords: traditional education; offline education; online education; online learning; e-learning; higher education; meta-analysis